Financial Resilience among Women Small and Medium Enterprise in Malaysia during and after COVID-19: The Role of Islamic Social Finance - Nur Farhah Mahadi; Muhammad-Bashir Owolabi Yusuf; Salina Kassim; Syarah Syahira Binti Mohd Yusoff (Bank Indonesia, 2024)
The COVID-19 pandemic disproportionately impacted women-owned small and medium enterprises (SMEs) in Malaysia, exposing their vulnerabilities and highlighting the need for effective resilience strategies. This study examines the role of Islamic social finance in enhancing the financial resilience of these businesses during and beyond the pandemic. To achieve this goal, the study explores three key areas i.e., identifying factors shaping the financial resilience of women-owned SMEs in Malaysia during and beyond the pandemic, assessing the effectiveness of Islamic social finance instruments in fostering financial resilience for these businesses, and formulating recommendations for effective policies that strengthen the financial resilience of women-owned SMEs, enabling them to navigate future pandemics more effectively. Using a Partial Least Squares Structural Equation Modeling (PLS-SEM) method and 330 respondents, we document no significant effects of Islamic social finance instruments on the financial resilience of women-owned SMEs. We argue that this documented insignificance could be due to the ways Islamic Social Finance (ISF) is operationalized. At the same time, contradicting previous research on the ISF women-owned SMEs financial resilience, we also believe that further investigation is needed. Acknowledgment This research is supported by the Ministry of Higher Education of Malaysia (MOE) through Fundamental Research Grant Scheme (FRGS/1/2021/SS01/UIAM/03/3).